Effects of whole body vibration exercise on muscle strength and dynamic balance on elderly people. - Vieira, I. (2017)
Introduction: One of the major causes generating disability and even death among the elderly population are the falls, and as such a major public health problem (Bogaerts, Delechulse, Boonen, Claessens, Milisen & Verschueren, 2011). There are several studies that show that the Whole Body Vibration (WBV) can be a reliable alternative to many other types of training to reduce the risk of falls of the elderly, by improving the muscle strength, balance capacity and mobility (Lam, Lau, Chung & Pang, 2012). Thus, the present study aims to find out what are the effects of the vibration training on muscle strength and dynamic balance in individuals over 65 years old. Methods: Thirty-one older people (age 70,2±6,3 years) were randomly assigned to an experimental group (n=16), performing 16 weeks, 2 weekly sessions of 30 min of exercise with warm up (5 min bycicle and 5 min 4 set of exercises) 30 sec x 4 sets of WBV with 60 sec of rest between sets; or to a control group (n=15). Maximal isokinetic strength was measured at 60º/s in the knee extensors and flexors in concentric action. Dynamic balance was evaluated using The Timed up and Go Test (Rikli & Jones, 1999). Results: After 16 weeks of WBV exercise significant improvements occurred in concentric extensors strength at 60º/s (≈17%) and in dynamic postural balance (≈16%) (Table 1). Multivariate regression analyses indicated that gains in concentric knee extensors strength predicted improvements of 35% in postural balance |F (2, 17) = 17,410; R2 = 0,351; p = 0.026)| Conclusions: A WBV exercise produced relevant gains in dynamic postural balance and muscle strength at low velocities of movements in extensors, some of which predicted improvements in dynamic balance which is important for daily activities such as, getting off a bus in time, to go to the bathroom or answer the phone.